Farmers’ own assessment of climate smart agriculture: Insights from Ma village in Vietnam - Vernooy, Ronnie; Le Kai Hoan; Tuan Cuong; Bui, Le Vinh (2018)
The project Integrated agricultural technologies for enhanced adaptive capacity and resilient livelihoods in climate-smart villages (CSVs) of Southeast Asia aims to provide climate-smart agriculture (CSA) options to enhance adaptive capacity and resilience among CSV farmers and stakeholders. In 2016, in Ma village in Vietnam, one of the CSVs in the region, monitoring and evaluation (M&E) activities focused on the social dimension of the action research: how key actors involved in the research are experiencing progress, costs and benefits, achievements and challenges. To date, M&E of the biophysical dimension by scientists and farmers has received little attention. Although scientists have developed a coherent analytical CSA framework that guides the field research, so far they have struggled to practically track and measure outcome results in a systematic way. This report documents and reflects on how woman and man farmers in Ma village are assessing the biophysical results of the climate-smart techniques and practices they have adopted. They do this mostly through direct observation, some measurement, “before and after” comparison, and some comparison with what neighbours are doing. Overall, farmers’ assessment appears positive despite the lack of quantitative precision to support their judgement. There is work to do for the CSA scientists.